The impact of the winery's wastewater treatment system on the winery water footprint - Saraiva, Artur (2019)
In the Mediterranean region, water scarcity has already prompted concern in the wine sector due to the strong impact it has on vineyard productivity and wine quality. Water footprint is an indicator that takes account of all the water involved in the creation of a product and may help producers to identify hotspots, and reduce water consumption and the corresponding production costs. In recent years several studies have been reported on wine water footprint determination, but mostly focused on the viticulture phase or assuming no grey water footprint at the winery since it has a treatment system. In the framework of the WineWaterFootprint project a medium-size winery was monitored, with direct measurements, regarding determination of the blue and grey components of water footprint. The determined winery water footprint ranged from 9.6 to 12.7 L of water per wine bottle of 0.75 L, the wastewater produced being responsible for about 98%, which means that the grey component cannot be disregarded. The developed scenarios show that a potential reduction of 87% in winery water footprint can be obtained with almost no investment. The challenge of reducing the grey footprint is not in technology development, but rather in the proper maintenance and monitoring of treatment systems.